Pengaruh Pemberian Madu terhadap Kolesterol Total - Mega Ulfiyah Noor; Fajar Prasetya; Febrina Mahmudah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Honey contains Vitamin C which is a natural antioxidant which can have the effect of lowering total cholesterol levels in the blood. This study aims to determine the characteristics of gender, age, and occupation of hypercholesterolemic respondents and to determine the effect of honey administration on reducing total cholesterol levels of hypercholesterolemic respondents in Palaran District, Samarinda. The research method used is quasy experimental and research procedures by measuring before and after being given treatment. Data collection on the characteristics of respondents obtained the highest percentage of women as much as 80%, age 46-55 years as much as 40%, and housewives as much as 75%. The results of descriptive analysis of total cholesterol levels in the pre-test gave an average result of 224.9 mg / dL and the post-test gave an average result of 202.1 mg / dL. Based on the research results, it can be concluded that honey can have an effect on reducing total cholesterol levels in the blood.